Factors Influencing the Utilization of Postnatal Care Services in the First Seven Days of Childbirth in Lalitpur District, Nepal - Pandey, Ambika; Yang, Min; Kapri, Sangita Pudasainee; Adhikari, Debendra P. (Journal of Nursing Education of Nepal, 2023)
Introduction: The utilization of postnatal care (PNC) is very important for improving the well-being of both the mother and the newborn, treating postnatal complications, and providing important care information. The purpose of this study is to identify factors affecting the utilization of PNC among postnatal mothers within the first seven days of childbirth.Methods: A cross-sectional study was conducted among 479 mothers of infants from urban and rural municipalities. Data were analyzed using SPSS version 20. Binary logistic regression was used to analyze the association between independent variables and PNC service utilization.Results: Only 25.1% were visited three times for PNC services by health workers within seven days of birth and about 12% never visited health institutions for PNC services. Results indicate that mothers who gave birth with the assistance of a physician (AOR = 6.687, 95% CI = 3.699, 12.087), who received information from healthcare workers (AOR = 2.297, 95% CI = 1.325, 3.985), who knew about postpartum complications (AOR = 2.216, 95% CI = 1.342, 3.659), and who had a business or service occupation (AOR = 1.803, 95% CI = 1.024, 3.175) were more likely to utilize three PNC visits within the first week after childbirth.Conclusion: Findings indicate low utilization of three PNC services within seven days of childbirth among postnatal mothers. Community-based education on the importance of three PNC services and postnatal complications during prenatal visits may enhance the utilization of PNC services among postnatal mothers in Nepal.DOI: https://doi.org/10.62143/6y1krc50